Microorganisms in human milk: lights and shadows. (19th September 2013) - Civardi, Elisa; Garofoli, Francesca; Tzialla, Chryssoula; Paolillo, Piermichele; Bollani, Lina; Stronati, Mauro
Abstract: Human milk has been traditionally considered germ free, however, recent studies have shown that it represents a continuous supply of commensal and potentially probiotic bacteria to the infant gut. Mammary microbioma may exercise anti-infective, anti-inflammatory, immunomodulatory and metabolic properties. Moreover human milk may be a source of pathogenic microorganism during maternal infection, if contaminated during expression or in case of vaccination of the mother. The non-sterility of breast milk can, thus, be seen as a protective factor, or rarely, as a risk factor for the newborn.